Práticas de resistência em Antônia : identidade, representação e exclusão social da mulher negra da periferia - Gomes, Viviane dos Santos (2010)
The social and political events have historically demanded reflection, specially regarding the way the media influences people's behavior and their way of thinking; the way they see themselves and the way they see the others, as well as the construction of identities (KELLNER 2001). Thus, studying the media to look for the comprehension of different forms of intersection between the media itself and such events was the main principle adopted to choose the thematic of this research: the practice of resistance in the identity constitution and representation of the poor black Brazilian woman on the televise media. Noticing this mobilization of the media in relation to this theme, the question that made us worried was if the series Antônia, in the singular way of a discursive event of the media, is a starter of a socio-cultural and political movement of statement that, unlike the past, builds in the present the post-modern, black Brazilian woman representation, awarding her recognized identities to the way of getting a subject throughout the history by the power of resistance. Trying to find possible answers for this questioning, we worked with three possible hypotheses: (i) the series Antônia is part of a rising cultural and esthetic movement in which the media tries to promote new representations of subjects who are excluded from the society, such as the black woman; (ii) the new representation of the black subjects in the national media gets its inspiration from the affirmative model constructed by the North-American media; (iii) the Antônia identity is highlighted by the differences present in the relationship man-woman, whose effects of truth give the male universe a supremacy over the female universe. In this way, based on the French Analysis of Discourse, according to Foucault's perspective of history, power, knowledge, production of subjects; and studies concerning the memory (DAVALLON, 199; ACHARD, 199); as well as the identity and difference in the post-modernity/liquid modernity (HALL, 2006; BAUMAN, 2001; SILVA, 2000; WOODWARD, 1999), among others theoretical devices, we opted for the series Antônia, shown at Rede Globo in 2006, as the object of this study because its conditions of existence allow - considering the relations of knowledge-power, history and memory - the comprehension of the processes of representation and the processes of constitution of the poor black woman's identity in the televise media, confirming the hypothesis about the identities built in the television concerning these marginalized subjects. Therefore, the main goal of this research is to understand how the identities and the representations of the Black Brazilian woman in the relations of knowledge/power, history and memory, in Antônia, are constituted in the post-modern period, moment in which there is a crises in the patriarchy regime and a glamorization of the poverty and violence in the media.